STRATEGI GURU DALAM MEMBENTUK KARAKTER NASIONALISME PADA SISWA MI NURUL HUDA BAKALAN BULULAWANG MALANG - Lu’luul Millati Afifah; Anwar Sa'dullah; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Shaping the character of nationalism is the way of Madrasah Ibtidaiyah teacher, and has supporting and inhibiting factors in shaping the character of nationalism. This research was conducted at the Madrasah Ibtidaiyah Nurul Huda Bakalan Bululawang Malang. The approach in this study is qualitative with descriptive research type, in collecting data researchers use observation, interviews, and documentation, data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of the teacher’s strategy research in shaping the character of nationalism in students are by a) instilling a sense of patriotism from an early age through learning PKN and IPS, b) instilling an attitude of nasionalism during flag ceremony activities, c) forming an attitude of nationalism through scout extracurricular activities, d) establish good character in students. Teachers in forming the character of nationalism there are several factors including supporting factors a) teachers, b) parents and teachers provide moral education, furthermore the inhibiting factors in shaping the character of nationalism include: a) lack of attention from parents, b) courtesy towards older.